Polarisation variation of linear polarised Bi‐ISAR system in space targets imaging - Linsheng Bu (IET Radar, Sonar & Navigation, 2021)
Abstract A bistatic inverse synthetic aperture radar (Bi‐ISAR) system is used to observe space targets through different viewing angles via a bistatic radar configuration. It is seen that the receiver of a linear polarised Bi‐ISAR system with a long baseline will encounter energy variation and high‐order phase deviation in ISAR imaging due to the polarisation variation of this system. Here, the authors quantitatively analyse the energy variation caused by polarisation mismatch in a linearly polarised Bi‐ISAR system by investigating the time‐varying bistatic angle and intrinsic variable polarisation effect of targets via the combination of observation geometry and computational electromagnetic. The high‐order phase deviation in long‐term coherent processing is also presented through the same strategy. The authors conducted simulations for a bistatic system, which is configured with different baseline vectors, to analyse the impact of polarisation variation of the linear polarised Bi‐ISAR system on the energy loss and high‐order phase terms.